Polymorphism-driven immune disruptions in Kawasaki disease across populations: decoding the role of T and B-cells - Zhang, Chu; Wang, Lu; Fan, Qihong; Pan, Yan (Frontiers in Immunology, 2025)
Kawasaki disease (KD) is a self-limiting, systemic vasculitic syndrome of unknown etiology that primarily affects children under the age of five, with notably high incidence in Asian populations. Although initial treatment with high-dose intravenous immunoglobulin (IVIG) and aspirin can reduce acute symptoms of KD and the risk of coronary artery lesions (CALs), diagnosis remains challenging due to the absence of specific biomarkers and the incomplete understanding of disease pathogenesis, often resulting in misdiagnosis or delayed intervention. Genetic predisposition and immune dysregulation, particularly involving B-cell and T-cell pathways, have been implicated in KD susceptibility and the development of CAL. This review summarizes current evidence on immune-regulatory gene polymorphisms, with a focus on how T-cell and B-cell–related genetic variations may contribute to disease onset and vascular complications. These insights may help inform improved diagnostic accuracy—particularly for incomplete KD—and support personalized treatment strategies, such as corticosteroids or anti-TNF agents in genetically high-risk patients.